Effect of Traditional Chinese Medicine on the Cardiovascular Diseases - Jiang, Yang; Zhao, Qi; Li, Lin; Huang, Shumin; Yi, Shuai; Hu, Zhixi (Frontiers in Pharmacology, 2022)
Background: Traditional Chinese medicine (TCM) is the health care system developed with the help of clinical trials that are based ideally on the scientific model of regulation. Objective: This systematic health care system relies on some specific unique theories and practical experiences to treat and cure diseases, thus enhancing the public's health. Review Methodology: The current review covers the available literature from 2000 to 2021. The data was collected from journals research articles, published books, thesis, and electronic databases, search engines such as Google Scholar, Elsevier, EBSCO, PMC, PubMed, ScienceDirect, Willey Online Library, Springer Link, and CNKI) searching key terms, cardiovascular disease, traditional Chinese medicines, natural products, and bioactive compounds. Full-length articles and abstracts were screened for the collection of information included in the paper. Results: Clinical trials on the TCM and basic research carried out on its mechanism and nature have led to the application and development of the perfect design of the research techniques, for example, twofold striking in acupuncture that aid in overcoming the limitations and resistances in integrating and applicability of these experiences and trials into the pre-existing biomedical models. Furthermore, TCM has also been utilized from ancient times to treat heart diseases in Asia, particularly in China, and is now used by people in many other areas. Cardiovascular Disease (CVD) is mainly developed by oxidative stress. Hence antioxidants can be beneficial in treating this particular disease. TCM has a wide variety of antioxidant components. Conclusion: The current review article summarizes the underlying therapeutic property of TCM and its mechanism. It also overviews the evidence of the mechanism of TCM action in CVD prevention by controlling oxidative stress and its signaling pathway.